Application of GPRS and GIS in Boiler Remote Monitoring System - Yifeng Wu; Hongchao Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
Application of GPRS and GIS in boiler remote monitoring system was designed in this paper by combining the advantage of GPRS and GIS in remote data transmission with configuration monitoring technology. The detail information of the operating conditions of the industrial boiler can be viewed by marking the location of boiler on the electronic map dynamically which can realize the unified management for industrial boiler of a region or city conveniently. Experimental application show that the system has convenience to use, high reliability, which play an active role to improve the operating efficiency, to prevent the boiler accident, and to decrease the energy consumption. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1655